Anticancer chemotherapies targeting Wnt/β-catenin signaling pathway: a review on molecular insights - Nguyen, Thi Quynh Huong; Tran, Thi-Kieu-Trinh; Nguyen, Vu-Quynh-Nhu; Pham, Thuy-Loc; Nguyen, Thi-Thuy; Ngo, Thi-Kieu-Diem; Vu, Thi-Tram; Pham, Thi-Phuong-Thao; Ha, Hai-Anh (Jurnal Ilmiah Farmasi, 2024)
Background: The Wnt/β-catenin signaling pathway, a highly conserved signaling axis involved in diverse physiological processes such as proliferation, differentiation, apoptosis, migration, invasion, and homeostasis balance, has been implicated in human cancer development and progression. Notably, various cancer types, such as colorectal cancer, hepatocellular carcinoma, melanoma, thyroid cancer, desmoid tumors, ovarian tumors, and multiple myeloma, have demonstrated associations with specific Wnt-activating mutations, emphasizing the widespread influence of the Wnt pathway in diverse malignancies. Objective: This review highlights the inhibitors targeting the Wnt ligand-receptor interface, focusing on their preclinical and clinical evaluations in various cancer types. Additionally, we explore small-molecule design strategies, focusing on inhibitors of β-catenin, GSK-3, and Porcupine. Method: Conducted as a narrative review, we collected and analyzed relevant papers from PubMed/Google Scholar and clinical trials associated with Wnt pathway inhibitors from clinicaltrial.gov. A total of 61 papers and 24 clinical trials were reviewed, providing an overview of the molecular insights within the research landscape of this field. Result: Dysregulated Wnt/β-catenin signaling is implicated in the progression of several solid tumors and hematological malignancies, highlighting the urgent need for targeted anticancer interventions. Our discussion on the inhibitors targeting the Wnt ligand-receptor interface highlights promising outcomes in both preclinical and clinical settings. This paper also presents the chemical structures of these compounds, detailing their interactions with key Wnt signaling components and their potential to disrupt aberrant signaling. The strategies for small-molecule design targeting the Wnt signal are discussed, highlighting inhibitors targeting β-catenin, GSK-3, and Porcupine. The complex chemical structures of these compounds are elucidated, showcasing their specific interactions with key components of the Wnt signaling pathway and their potential to disrupt aberrant Wnt signaling in diverse cancer types. The emerging directions and future prospects in Wnt pathway research demonstrate the importance of utilizing big data and artificial intelligence for drug development. Conclusion: The review delves into the potential inhibition of the disheveled protein as a promising target for cancer therapy, proposing novel molecular design strategies based on recent discoveries. Keywords: Wnt signaling pathway, β-catenin inhibitors, GSK-3 inhibitors, porcupine inhibitors, Disheveled protein inhibitors